Incidence and Survival After In-Hospital Cardiopulmonary Resuscitation in Nonelderly Adults: US Experience, 2007 to 2012. (February 2017) - Mallikethi-Reddy, Sagar; Briasoulis, Alexandros; Akintoye, Emmanuel; Jagadeesh, Kavyashri; Brook, Robert D.; Rubenfire, Melvyn; Afonso, Luis; Grines, Cindy L.
Abstract : Background—: Survival trends after in-hospital cardiopulmonary resuscitation (ICPR) for cardiac arrest in nonelderly adults is not well known. Influence of cardiopulmonary resuscitation guidelines on nationwide survival after ICPR is yet to be well elucidated. Methods and Results—: We examined survival trends and factors associated with survival after ICPR in nonelderly adults aged 18 to 64 years, using Healthcare Utilization Project Nationwide Inpatient Sample Database from 2007 through 2012 in the United States. Furthermore, we studied the impact of 2010 American Heart Association cardiopulmonary resuscitation guidelines on survival. We identified 235 959 patients who underwent ICPR after cardiac arrest. Overall, 30.4% patients survived to hospital discharge. Survival improved from 27.4% in 2007 to 32.8% in 2012 ( P trend <0.001). Shockable arrest rhythms were noted in 23.3% of patients. Incidence of ICPR increased from 1.81 per 1000 hospitalizations in 2007 to 2.37 per 1000 hospitalizations in 2012 ( P trend <0.001). There was no statistically significant change in survival trends before and after 2010 cardiopulmonary resuscitation guidelines. Female sex and shockable rhythms were associated with higher adjusted odds of survival, whereas black race, lack of health insurance, age, and weekend admission were associated with lower adjusted odds of survival. Conclusions—: Among nonelderly adults, survival after ICPR improved significantly from 2007 through 2012, with an overall survival rate of 30.4%. Incidence of ICPR increased significantly during the study period. There was no statistically significant change in survival before and after 2010 cardiopulmonary resuscitation guidelines. Female sex and black race were associated with higher and lower odds of survival, respectively. Abstract : Supplemental Digital Content is available in the text.